Fetal Scalp Cyst or Small Meningocele: Differential Diagnosis with Three-Dimensional Ultrasound - Sepulveda, W (2011)
Background: Prenatal differential diagnosis of fetal scalp cystic masses is challenging and mainly includes small meningoceles and epidermal cysts. Case: A second-trimester anatomy scan revealed an extracranial cystic mass measuring 17 × 12 × 10 mm in the fetal occipital region. Three-dimensional datasets were obtained transabdominally and off-line analysis revealed a connection between the cyst and the subarachnoid space through a 5-mm skull defect. The diagnosis of a small meningocele was further confirmed by magnetic resonance imaging in the infant. Conclusion: Prenatal three-dimensional ultrasound can be a useful adjunct in the prenatal differentiation between small meningoceles and epidermal cysts. Copyright © 2011 S. Karger AG, Basel.